Performance of energy and protein metabolism of female water buffaloes during early postpartum period - Gallego, C.; Fraga, L. M.; Peñalver, A.; García, A.; López, R. G.; Lens Souza, María Inés; Oba, Eunice (Cuban Journal of Agricultural Science, 2019)
An amount of 30 crossbred female buffaloes was used to evaluate blood levels of glucose, cholesterol, triglycerides, total proteins and urea during the first eight weeks postpartum. Blood samples were obtained from the jugular vein once a week. Biochemical analyzes were performed through the enzymatic calorimetric method and readings were carried out by absorption spectrophotometry. A mixed generalized linear model was used. Postpartum weeks showed a significant effect on the performance of serum indicators (P <.0001). Different was observed for the number of parturitions and milk production during the first 60 days. There was an increase (P <.0001) of glycemia (2.67 - 3.62 mmol/L) and uremia (6.15 - 6.81 mmol/L) from the first to the fifth and sixth week, respectively, although a gradual decrease was observed in the subsequent weeks. Cholesterol (1.04 - 1.80 mmol/L) and triglycerides (0.26 - 0.80 mmol/L) concentrations showed continuous increase during the study (P <.0001). Total proteins showed decrease (P <.0001) in their concentrations from the first to the fifth week (82.48 - 76.76 g/L), while a progressive increase was observed in the following weeks. It was demonstrated that, during the first eight postpartum weeks, there are variations in the concentrations of energy and protein metabolism indicators in buffaloes, mainly due to the increase of milk production and mobilization of their body reserves, as a consequence of metabolic imbalance between nutrient income and energy required. Keywords: female buffaloes, blood indicators, lactation, postpartum